Local Well-Posedness for the Compressible Nematic Liquid Crystals Flow with Vacuum (Analysis in Theory and Applications, 2020)
In this paper we prove the local well-posedness of strong solutions to the compressible nematic liquid crystals flow with vacuum in a bounded domain $Ω\subset \mathbb{R}^3$.
Keywords: Liquid crystals; vacuum; Local well-posedness; strong solution.